The Principles of Business Continuity and Public Interest in the Resolution of Sharia Bankruptcy Disputes - Marsetiaji, M.; Arif Khan, M. Dawud; Hidayat (Manunggal Halim Jaya, 2026)
The background of this study lies in the absence of specific regulations regarding bankruptcy and the suspension of debt payment obligations (PKPU) based on Sharia principles. In practice, the principles of business continuity and public interest (maṣlaḥah) are often neglected in resolving Sharia bankruptcy disputes, leading judges to focus primarily on formal juridical aspects. This research aims to analyze the implementation of these two principles in PKPU cases involving Sharia contracts, which the Commercial Court and the Supreme Court handle. The study employs a qualitative method with a normative legal approach through document studies and interviews. The results indicate that the principle of business continuity has not been optimally applied, while the principle of public interest is often overlooked in legal considerations. These findings underscore the need to reformulate Sharia bankruptcy law to incorporate maqāṣid al-syarī‘ah values better, thereby providing judges with a stronger foundation for balancing the interests of debtors, creditors, and society fairly and equitably.